Analysis of loss of water inventory at the Philippine research reactor 1-fuel storage facility. - Gatchalian, Ronald Daryll E.; Astronomo, Alvie A.; Olivares, Ryan U.; Mangulabnan, Dan Beth C. (2021)
"The Philippine Research Reactor-1 (PRR-1) fuel storage facility is a wet storage for the irradiated nuclear fuel. The behavior of the facility in case of accidental loss of water is currently unknown. Safety analysis of a repository of fissile material involves critically safety assessment and radiation dose estimation for normal and accident scenarios"-title page.
Includes bibliographical references.
Keywords: Effective multiplication factor; Monte Carlo method; TRIGA reactors